Character of Christian-Muslim Encounter - Pratt, Douglas. (The History of Christian-Muslim Relations, 2015)
The Character of Christian-Muslim Encounter is a Festschrift in honour of David Thomas , Professor of Christianity and Islam, and Nadir Dinshaw Professor of Inter Religious Relations, at the University of Birmingham, UK. The Editors have put together a collection of over 30 contributions from colleagues of Professor Thomas that commences with a biographical sketch and representative tribute provided by a former doctoral student, and comprises a series of wide-ranging academic papers arranged to broadly reflect three dimensions of David Thomas' academic and professional work - studies in and of Islam; Christian-Muslim relations; the Church and interreligious engagement. These are set in the context of a focussed theme - the character of Christian-Muslim encounters - and cast within a broad chronological framework. Contributors, excluding the editors, are: Clare Amos, John Azumah, Mark Beaumont, David Cheetham, Rifaat Ebied, Stanisław Grodź SVD, Alan Guenther, Damian Howard SJ, Michael Ipgrave, Muammer İskenderoğlu, Risto Jukko, Alex Mallett, Juan Pedro Monferrer-Sala, Lucinda Mosher, Gordon Nickel, Jørgen Nielsen, Claire Norton, Emilio Platti, Luis Bernabé Pons, Peniel Rajkumar, Peter Riddell, Umar Ryad, Andrew Sharp, Sigvard von Sicard, Richard Sudworth, Mark Swanson, Charles Tieszen, John Tolan, Davide Tacchini, Herman Teule, Albert Walters.